2016
DOI: 10.1016/j.arabjc.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel l-amino acid ionic liquid for quick and highly efficient synthesis of oxime derivatives – An environmental benign approach

Abstract: A mild, efficient, and eco-friendly procedure for the conversion of aliphatic, alicyclic and aromatic carbonyl compounds into the corresponding oximes, was catalyzed by a novel imidazolium based ionic liquid coupled with amino acid (asparagine) (L-AAIL, L-Amino acid functionalized ionic liquid) catalytic system. The quantitative conversion of aryl and alkyl carbonyl compounds into the corresponding oximes was achieved by simply grinding at ambient temperature using 0.05 mmol of catalyst in 50 s. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As the catalyst, amino acid ionic liquids have many advantages, such as low temperature activity, mild reaction conditions, friendly environment, and high selectivity. Parasuraman et al [7] reported that the ionic liquid synthesized from Lasparagine and 1-(2-aminoethyl)-3-methylimidazolium bromide was used to catalyze the conversion of aliphatic, alicyclic, and aromatic carbonyl compounds to corresponding oximes. This process was achieved by simply grinding at ambient temperature using 0.05 mmol of catalyst in 50 s, and the yield is up to 96%.…”
Section: Catalystmentioning
confidence: 99%
“…As the catalyst, amino acid ionic liquids have many advantages, such as low temperature activity, mild reaction conditions, friendly environment, and high selectivity. Parasuraman et al [7] reported that the ionic liquid synthesized from Lasparagine and 1-(2-aminoethyl)-3-methylimidazolium bromide was used to catalyze the conversion of aliphatic, alicyclic, and aromatic carbonyl compounds to corresponding oximes. This process was achieved by simply grinding at ambient temperature using 0.05 mmol of catalyst in 50 s, and the yield is up to 96%.…”
Section: Catalystmentioning
confidence: 99%
“…Actually, this byproducts is one of the main issue of the whole process [1,2]. Recently, literature have reported new methodologies giving good yields in ketones oximation carried out in ionic liquids, so that avoiding the neutralization [9]. Besides organocatalysts improves such a step by increasing the yield in the oximes formation, particularly useful for ketones with low reactivity, especially for those with steric hindrance at the carbonyl.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the chemistry of trifluoroacetic acid as organocatalyst has been suggested for the synthesis of the caprolactam, of other amides as well as to several other reactions of industrial interest [7][8][9][10][11][12][13][14][15][16]. For instance, some authors proposed the direct oximation and rearrangement of ketones and in particular, of the cyclohexanone, to the corresponding amides [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present a highly selective oxidation of 1-propanol to propionic acid with high conversion, using a recyclable organic-inorganic heteropolyoxometalate as the catalyst and H 2 O 2 as the oxidant. Inexpensive and readily available amino acid is selected as the cation [26][27][28]. Moreover, its weak acidity can provide a suitable catalytic environment.…”
Section: Introductionmentioning
confidence: 99%